Description of Interprofessional Collaboration Between Pharmacists and Doctors in Management of TBC Patients in Community Health Lombok Island - Maghfirahandini, Reivirly Khairadaty; Andanalusia, Mahacita; Adni, Azizatul; Saputra, Yoga Dwi (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Tuberculosis (TB) remains a priority health problem in Indonesia, with West Nusa Tenggara Province reporting 11,061 cases in 2023, most of which originated from Lombok Island. TB treatment success rates in this region remain below national targets, necessitating effective interprofessional collaboration between physicians and pharmacists as key players in therapy management. This study aims to describe the interprofessional collaboration between pharmacists and physicians in TB patient management at community health centers (Puskesmas) across Lombok Island. The study used a quantitative descriptive method involving 54 pharmacists selected through purposive sampling. The instrument used was the Pharmacist–Physician Collaborative Index (PPCI), which assesses three main domains: trust, initiating relationships, and role specification, as well as one additional domain: collaborative practice. Analysis was conducted descriptively based on the categorization scores for each domain. The results showed that the level of collaboration was in the moderate category. The trust domain was in the moderate category, the initiating relationship was in the moderate category, and the role specification was in the adequate category. Overall, collaborative practices were deemed quite effective. These results indicate that although collaboration has been established, improvements in communication, role clarity, and consistent information exchange are still needed to support optimal TB management in community health centers.